ENSAYO SOBRE EL COMERCIO AMBULATORIO COMO FALLA DEL MERCADO COMPETITIVO EN EL PERÚ - Muñoz Estrada, Darwin Elviro (2021)
The economic science determines that the market is efficient if it complies with the following principle, as well as the suppliers and demanders cannot influence the prices, that is why the mar-kets are determined by the prices, in these conditions the first fundamental theorem about the welfare economy, that in cer-tain circumstances the market is efficient in the Pareto sense.